2019
DOI: 10.1177/1744987119877421
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of happiness and professional autonomy in Iranian nurses

Abstract: Background Happiness and professional autonomy in nurses increase job satisfaction, reduce turnover and improve the quality of healthcare services. Aims The present study aimed to examine the correlation between happiness and professional autonomy in Iranian nurses. Methods This descriptive-correlational study was conducted on 371 nurses in 2017. The participants were selected via two-step random sampling. Data were collected using the Oxford Happiness Inventory and Dempster Practice Behaviors Scale within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…The restricted professional autonomy perceived by nurses, which impeded CT, may be different for each culture or country. For instance, several studies in Asia have reported that nurses lack or have limited authority in providing care for their patients [ 30 , 31 ]; furthermore, while CT allows nurses to generate new ideas quickly, become more flexible, and act independently and confidently, the scope of their action is still ultimately limited by the physician’s clinical decisions [ 10 ]. Thus, several Asian nursing scholars have stressed the growth of professional autonomy among nurses through exercising higher levels of CT as an area that needs support to improve nurses’ clinical competence.…”
Section: Discussionmentioning
confidence: 99%
“…The restricted professional autonomy perceived by nurses, which impeded CT, may be different for each culture or country. For instance, several studies in Asia have reported that nurses lack or have limited authority in providing care for their patients [ 30 , 31 ]; furthermore, while CT allows nurses to generate new ideas quickly, become more flexible, and act independently and confidently, the scope of their action is still ultimately limited by the physician’s clinical decisions [ 10 ]. Thus, several Asian nursing scholars have stressed the growth of professional autonomy among nurses through exercising higher levels of CT as an area that needs support to improve nurses’ clinical competence.…”
Section: Discussionmentioning
confidence: 99%
“…The study determined that the happiness levels of the participants are above average. Research conducted by Nam and Know (2013) and Mousavi et al (2018) also determined the happiness levels of the participants to be at a good level. In a study by Hwang (2019), it was found that the happiness levels of the participants were low.…”
Section: Discussionmentioning
confidence: 99%
“…Happiness at work means that the employee enjoys his job and loves what he does at work. It is expressed that happiness in the workplace is related to job satisfaction, and happy employees are more satisfied with their jobs than unhappy ones (Duche Pérez & Rivera Galdos, 2019; Hwang, 2019; Mousavi et al, 2018; Stoia, 2016). There is also evidence in the literature that happiness is associated with positive outcomes in different life spheres, including health, performance at work and income.…”
Section: Happinessmentioning
confidence: 99%
“…Today, with the development of the times and the improvement of medical level, people's pursuit of high‐quality health is becoming more and more urgent, which brings greater challenges to the medical and health field. As the largest component of the healthcare system, the nursing group plays an important role in the sustainable development of human health (Mousavi et al, 2019; Xue et al, 2022). As the guardians of human health, nurses serve the public's life and death, and play an irreplaceable role in preventing illness, promoting healings and alleviating sufferings (Shah et al, 2021).…”
Section: Introductionmentioning
confidence: 99%